COMPLEXES OF LEAD (II)*: CRYSTAL STRUCTURES OF L2Pb (NO,), AND L2Pb(SCN), L=Z(AMINOMETHYL) PYRIDINE (Journal of Sciences, Islamic Republic of Iran)
The reactions of Pb(N0 ) and Pb(SCN)2 with 2-(aminomethy1)pyridine (C H N = L) yielded colourless crystals of L Pb(N0 ) ( I ) and L Pb(SCN) , (2), respectively. Their structures were determined by X-ray crystallography. Crystal data: 1, monoclinic, P2 /c, a = 9.263 (4) ?, b = 7.783 (2) ?, c = 6.692 (3) ?, ? = 101.26 (2)?, Z = 2, Mo K?, 1540 observed (I > 2.5 ?(I) data (22 ? C), R = 0.038; 2, monoclinic P2 /c, a = 10.010 (3) ?, b = 8.212 (10) ?. c = 11.010 (5) ?, ?= 94.26 (5) ?, Z = 2, Mo K? 1856 observed (I > 2.5 ? ( I )) data (22 ? C), R = 0.040